Evaluation of the effects of emotional intelligence status on the communication skills of the faculty of medicine students - TOPUZOĞLU, AHMET; KURNAZ AY, MERVE (MARMARA UNIV, FAC MEDICINE, 2021)
Objective: In this study, we aimed to evaluate the emotional intelligence levels of the faculty of medicine students and to determine the effects of emotional intelligence levels on communication skills, and the effect of sociodemographic factors on emotional intelligence and communication skills. Materials and Methods: The faculty of medicine students constituted the sample of this descriptive study. The research was completed with a total of 225 students selected by the haphazard sampling method from each year of a six - year medical school. The data were collected using a questionnaire consisting of sociodemographic characteristics, the Emotional Intelligence Assessment Scale (ETAS), and the Communication Skills Evaluation Scale (CSES). Results: In our study, 44.4% (n = 100) of the participants were male , 55.6% (n = 125) were female. Approximately, 46.7% (n = 105) had low, 44.4% (100) had normal and 8.9% (n = 20) had high emotional intelligence. The communication skills mean score was found to be statistically significantly higher in female than in male. There was a moderate level of a positive correlation between emotional intelligence and communication skills. Conclusion: In conclusion, participants with a high level of emotional intelligence have better communication skills. In training programs, more emphasis can be given to emotion management, emotional intelligence, and communication skills.
Keywords: Emotional intelligence; Communication; Medicine; Students; Empathy; PERFORMANCE; EMPATHY